National predictors of hedgehog Erinaceus europaeus distribution and decline in Britain - Pettett, C; Johnson, P; Moorhouse, T; Macdonald, D (Wiley, 2017)
We utilise a volunteer survey recording roadkills between 2001 and 2011 to examine the factors affecting hedgehog Erinaceus europaeus abundance and decline. Hedgehogs were most abundant in the North and East of England and in Scotland, regions characterised by low badger numbers. Hedgehogs selected arable land and urban areas relative to their availability. Badger Meles meles and fox Vulpes vulpes abundance were negatively associated with hedgehog abundance at the 10 km2 scale. At the county level, foxes were positively associated with hedgehog numbers and badgers negatively associated. The mechanism behind the relationships between hedgehogs and badgers and foxes merits further investigation.